Optimization of Initial Dose Regimen for Sirolimus in Pediatric Patients With Lymphangioma - Chen, Xiao; Wang, Dongdong; Wang, Guangfei; Huang, Yidie; Yu, Xin; Lu, Jinmiao; Zhai, Xiaowen; Xu, Hong; Li, Zhiping (Frontiers in Pharmacology, 2021)
Sirolimus is an effective oral treatment for pediatric patients with lymphangioma. The present clinical study in 15 children (0.12 to 16.39 years of age) examines the effects of underlying factors on sirolimus concentrations through application of a population pharmacokinetic model. Using Monte Carlo simulation, an initial dose regimen for sirolimus in pediatric patients with lymphangioma is presented. It is found that the lower the body weight, the higher the clearance rate and sirolimus clearances are 0.31-0.17 L/h/kg in pediatric patients with lymphangioma whose weights are 5-60 kg, respectively. The doses of sirolimus, 0.07, 0.06, 0.05 mg/kg/day are recommended for weights of 5-10, 10-24.5 and 24.5-60 kg in children with lymphangioma. This study is the first to establish a population pharmacokinetic model for sirolimus and to recommend initial doses in pediatric patients with lymphangioma. Large scale, prospective studies are needed in the future.